GE_GERICHTE P/354/2017 vom 13. Dezember 2019 - GE Cour de justice (2019)
ASSASSINAT;TENTATIVE(DROIT PÉNAL);AGRESSION;VOL(DROIT PÉNAL);RESPONSABILITÉ(DROIT PÉNAL);ACTIO LIBERA IN CAUSA;EXPULSION(DROIT PÉNAL) | CP.112; CP.134; CP.139; CP.22; CP.19.al2; CP.19.al4; CP.66a.al2